The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1007/s00366-021-01514-4
|View full text |Cite
|
Sign up to set email alerts
|

Thermal post-buckling analysis of graded sandwich curved structures under variable thermal loadings

Abstract: In the present research, finite element solutions of thermal post-buckling load-bearing strength of functionally graded (FG) sandwich shell structures are reported by adopting a higher-order shear deformation type kinematics. For the numerical calculation, nine nodes are considered for each element. A specialized MATLAB code is developed incorporating the present mathematical model to evaluate the numerical buckling temperature. The Green-Lagrange nonlinear strain is adopted for the formulation of the sandwich… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 58 publications
(55 reference statements)
0
3
0
Order By: Relevance
“…Basing on the CST, strain components of the TSS are expressed aswherein which u,v and w are displacement components in the x,y and z directions, respectively. The Green-Lagrange nonlinear strain gives more accurate predictions and is usually adopted in numerical approaches, for examples in works of Kar and Panda 56 and Sahoo et al 57,58 Owing to less cumbersomeness and acceptable accuracy, von Kármán–Donnell nonlinear strain is widely used in many studies, e.g. works.…”
Section: Basic Equationsmentioning
confidence: 99%
“…Basing on the CST, strain components of the TSS are expressed aswherein which u,v and w are displacement components in the x,y and z directions, respectively. The Green-Lagrange nonlinear strain gives more accurate predictions and is usually adopted in numerical approaches, for examples in works of Kar and Panda 56 and Sahoo et al 57,58 Owing to less cumbersomeness and acceptable accuracy, von Kármán–Donnell nonlinear strain is widely used in many studies, e.g. works.…”
Section: Basic Equationsmentioning
confidence: 99%
“…The smoothing of the stress distribution is another of these benefits. Subsequently, several studies have been realized to investigate the linear and nonlinear static, buckling and vibration responses of FGM micro/nano-structures due to the increased relevance of the functionally graded materials structural components in the design of engineering structures [1][2][3][4][5][6][7]. Melaibri et al [8] demonstrated the vibrationala frequency behaviour of single walled carbon nanotubes (SWCNTs) shells by employing a modern analytical solution based on the Galerkin approach.…”
Section: Introductionmentioning
confidence: 99%
“…In order to study and observe the low velocity impact energy response of sandwich structures used for railways, Sakly et al [31] introduced finite element method (FEM), to simulate ballast impacts, a high-speed and low weight test bench was designed. The graded sandwich shell structure's thermal eigenvalue responses are numerically assessed under varied thermal loadings while considering temperature-dependent characteristics as investigated by Sahoo et al [32]. He et al [33] carried out experimentally and numerically the low velocity effect of carbon fiber face sheets and aluminum alloy cores.…”
Section: Introductionmentioning
confidence: 99%